Recognition of Three Common Work-Related Hand Diseases in a Teaching Hospital - Mitprasit, Amporn; Aekplakorn, Wichai; Kanchanathepsak, Thepparat; Srijareontham, Sawanee; Wongrathanandha, Chathaya (Biomedical Sciences and Clinical Medicine, 2025)
Objective Musculoskeletal disorders (MSDs) of the hands are increasingly affecting workers in various occupations. They reduce productivity and cause economic loss. In Thailand, work-related MSDs are considered underdiagnosed and under-reported. This study aimed to determine the proportion of three major recognized hand diseases that are work-related and to examine factors associated with that recognition and work-relatedness. Methods This is a cross-sectional study, recruiting and interviewing patients with carpal tunnel syndrome (CTS), trigger finger (TF), and de Quervain’s tenosynovitis (DQT) aged 18-65 years old who visited the Hand Clinic in the Orthopedics Department, Ramathibodi Hospital between 25 October 2023 and 15 March 2024. Patient medical records were reviewed to determine work-relatedness using NIOSH criteria. Recognition was determined by taking patient work histories. Logistic regression was used to examine the associations between work and MSDs, and between recognition and patients’ factors. Results A total of 270 patients were included: 127 CTS cases, 96 TF cases, and 47 DQT cases. Almost two-thirds (63.0%) of the diseases were attributed to work-related conditions. Factors associated with work-relatedness of the three diseases were: working for 26 or more hours per week (adjusted ORs 3.26-4.63), tool use (ORadj 7.92, 95%CI [2.83, 22.17]), computer use (ORadj 4.72, 95%CI [1.84,12.14]), writing (ORadj 4.88, 95%CI [1.53, 15.61]), and having a single job (ORadj 10.13, 95%CI [2.59,39.57]). The proportion of recognition by physicians of the connection between working history and MSDs was only 13.0%. There were no significant associations between patients’ personal/work factors and recognition by doctors. Conclusions This study showed that 63.0% three common hand diseases of patients are attributed to work-related conditions, but the recognition by doctors of that relationship was only 13.0%. Factors associated with work-relatedness were mostly aspects of patients’ work. The hospital should improve its system for identifying the work-related MSDs to help ensure patients receive appropriate health-related welfare and benefits. Further studies should be conducted to explore means of increasing physician recognition of work-related MSDs.